Perlindungan Pantai melaui Penanaman Mangrove di Pantai Pasir Puncu Purworejo Jawa Tengah - Rawana Rawana (Humanism: Journal of Community Empowerment (HJCE), 2022)
A mangrove ecosystem has a vital role in aquatic and terrestrial ecosystems. The goal of the activity is to protect the coastal area of Pasir Puncu due to intrusion, abrasion, tsunami wave, and salty wind, and to sequestrate and restore carbon stock in the mangrove ecosystem. The method of this activity was to plant with mangrove species seedling tied the bamboo stick. With a plant spacing of 1 x 1 m2; the number of mangrove species was 308 seedlings which has 6 months, and has 2-4 leaves. This planting program was carried out by Mangrove Instiper Club students. The result of this programme are planting R. mucronata, Avicennia marina, and Sonneratia alba of 300, 5, 3 seedlings respectively; Seedlings that have been planted are tied using bamboo stick with a length of 1 m using raffia rope. Selecting the mangrove species and site are the significant factors for survival mangrove seedling in the planting site. Keywords : Abrasion, carbon stock, mangrove, tsunami.